ПСИХОЛОГИЧЕСКИЕ ПРИНЦИПЫ РАЗВИТИЯ КОММУНИКАТИВНОЙ КОМПЕТЕНТНОСТИ У ВОСПИТАТЕЛЕЙ ДОШКОЛЬНЫХ ОБРАЗОВАТЕЛЬНЫХ ОРГАНИЗАЦИЙ (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article analyzes the psychological and practical aspects of communicative competence and its development in organizations, particularly in educational institutions. The author examines various aspects of communication, interaction, and the necessity of enhancing individuals' communicative abilities through modern methods, including communication technologies. The article also discusses the development of the concept of competence and its impact on pedagogical activities, as well as the interaction of communication in both individual and group environments.